(3GdEVQGH heHOC GSJeQGQjI GdeQab GdYGe (B: s (3OQGSI ebGQfI eY GdGgJeGe HGdLRGFQ haQfSG (B/ s - (3HQJjeI YHO GdhgGHs; (3CMeO MSf GdHQYi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3JXgQ CgejI GdOQGSI Mhd GdJhajb hGdJfGSH Hjf GdMb GdNGU (B- (3GdMb GdEVQGH (B- (3hGdeUdMI GdYGeI GdeJhNGI ef GSJeQGQjI GdeQab GdYGe hGdHMK Yf VeGf GdJhGRf Hjf GdMb hGdeUdMI hgd jLO gPG GdJhGab GdUYH hGdVQhQi MdI ai EjLGO ebGjjS GdMO GdCOfi ef GdNOeI? hGSJgOaJ GdOQGSI ddELGHI Ydi GdJSGDd GdQFjSi hGdJSGDdGJ GdaQYjI hGTJed GdHMK Ydi (B: (3GdEVQGH hGdeQab GdYGe hGdJhGab Hjf GdEVQGH heHOC GSJeQGQjI GdeQab GdYGe (B"(3GdMO GdCOfi ef GdNOeI(B" (3GdPi bSe Gdi eaghe GdMO GdCOfi ef GdNOeI ai GdeQab GdYGe hEYeGd GdMO GdCOfi ef GdNOeI CKfGA GdEVQGHs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2009.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B260 - 281.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdGLJeGYjIs; (3GdEVQGH s; (3GdGYJQGa GdOhdj HGdEVQGHs; (3EVQGH Yfb GdRLGLIs; (3GdeQab GdYGes; (3GdEVQGH aj GdbGfhf GdLRGFQjs; (3GdEVQGH hGSJeQGQjI GdeQab GdYGes; (3GdefXeGJ GdfbGHjIs; (3GdGJaGbjGJ GdLeGYjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs